MiR‐760 exerts an antioncogenic effect in esophageal squamous cell carcinoma by negatively driving fat metabolism via targeting c‐Myc. Issue 4 (10th November 2019) - Yang, Xuetao; Zhang, Cheng; Tie, Hongtao; Luo, Jun; Wang, Yiyang; Wu, Qingchen
Abstract: miR‐760 is downregulated in various human tumors, and fat metabolism disorder correlates with tumor progression, especially anomalism of key fat metabolic enzymes that are positively modulated by c‐Myc. The aim of our study is to elucidate the presumptive molecular mechanisms of miR‐760‐mediated esophageal squamous cell carcinoma (ESCC) cell function and to assess the therapeutic significance of miR‐760 in ESCC patients. Quantitative real‐time PCR (RT‐qPCR) analysis indicated that miR‐760 was significantly downexpressed in ESCC tissues and cell lines. Cell counting kit‐8 (CCK‐8) assay, colony formation assay, transwell assay, and flow cytometry denoted that induced ectopic overexpression of miR‐760 dramatically inhibited ESCC cells proliferation, attenuated migration, and invasion facilitated apoptosis in vitro. Mechanistically, c‐Myc predicted using bioinformatics was identified as a potential target gene of miR‐760 by luciferase reporter assay. Furthermore, mRNA and protein expression levels of c‐Myc and key fat metabolic enzymes were downregulated with miR‐760 mimics. The above investigation results, responsible for the antineoplastic properties of miR‐760 in ESCC, preliminarily highlighted that the hypothetical signal amongst miR‐760, c‐Myc, and key fat metabolic enzymes may develop a novel diagnostic marker, therapeutic target, and independent prognostic indicator. Abstract : MiR‐760 induces apoptosis and inhibits proliferation, migration, and invasion of ESCC cells. MiR‐760 performs the function as tumor‐suppressor by targeting c‐Myc. Fat metabolic key enzymes are negatively regulated by miR‐760 blocking c‐Myc.